Possible actions of methionine on embryonic development and postnatal phenotype of calves produced after embryo transfer - Masroor Sagheer; Quinn A. Hoorn; Oscar A. Ojeda-Rojas; Jeremy Block; Abigail J. Sproull; Daniella Heredia; Camila J. Cuellar; Tatiane S. Maia; McKenzie LJ. Haimon; Mariângela Bueno Cordeiro Maldonado; João H. Bittar; Angela M. Gonella-Diaza; et al. (Theriogenology, 2026)

From pioneers to disciples: Geoarchaeology in the eastern sector of the La Plata basin - Carola Castiñeira Latorre; Adriana M. Blasi; Irina Capdepont Caffa; Marco Alvarez; Diego Block (Journal of South American Earth Sciences, 2026)

Copepod population restarts: naupliar recruitment phenology during the winter-to-spring transition - Lauren N. Block; Alexandra M. Poje; Russell R. Hopcroft; Petra H. Lenz (Progress in Oceanography, 2026)

A quasi-differential measurement of neutron scattering from tantalum between 0.65 MeV and 20 MeV - Gregory J. Siemers; Yaron Danon; Sukhjinder Singh; Katelyn C. Keparutis; Peter J. Brain; Benjamin H. Wang; Adam M. Daskalakis; Devin P. Barry; Michael J. Rapp; Robert C. Block (Annals of Nuclear Energy, 2025)

Prediction of assistance dog training outcomes using machine learning and deep learning models - Mohammad Hossein Amirhosseini; James A. Serpell; Emily E. Bray; Theadora A. Block; Laura E.L.C. Douglas; Brenda S. Kennedy; Katy M. Evans; Kathleen Freeberg; Piya Pettigrew (Applied Animal Behaviour Science, 2025)

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

Unresolved resonance parameter evaluation and uncertainty quantification of n + 181Ta reactions - Jesse M. Brown; Devin P. Barry; Amanda Lewis; Timothy H. Trumbull; Marco T. Pigni; Travis Greene; Robert C. Block; Alec Golas; Yaron Danon (Annals of Nuclear Energy, 2025)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Effects of mycobacterium cell wall fraction on embryo development following in vitro embryo production and pregnancy rates following embryo transfer in virgin dairy heifers - W. Brown; M. Oliveira; R. Reis Silva; K. Woodruff; B. Bisha; D. Demetrio; J. Block (Theriogenology, 2024)

Archaeal blooms and busts in an estuarine time series - Justin T. Guider; Kristin M. Yoshimura; Kaleigh R. Block; Jennifer F. Biddle; Sunita R. Shah Walter (Environmental Microbiology, 2024)
Coastal bays, such as Delaware Bay, are highly productive, ecologically important transitions between rivers and the coastal ocean. They offer opportunities to investigate archaeal assemblages across seasons, with the exchange of water masses that occurs with tidal cycles, and in the context of variable organic matter quality. For a year‐long estuarine, size‐fractionated time series, we used amplicon sequencing, chemical measurements, and qPCR to follow archaeal groups through the seasons. We detected seasonally high abundances of Marine Group II archaea in summer months which correlate with indicators of phytoplankton production, although not phytoplankton biomass. Although previous studies have reported associations between Marine Group II archaea and particles, here they are almost entirely found in very small particles (0.22–0.7 μm), suggesting they are free‐living cells. Populations of Nitrososphaeria did not vary with particle size or environmental conditions. Methanogens were significant fractions of archaeal sequences in large particles at low tide during winter months. Contrary to expectations, Nanoarchaeia were found predominantly in the free‐living fraction despite the previous observation that they require an association with hosts. These results underscore the utility of time series studies in shallow, tidally mixed estuarine environments that capture variable conditions for understanding the ecology and biogeochemistry of planktic archaea.

Enhanced detection of mpox virus in wastewater using a pre-amplification approach: A pilot study informing population-level monitoring of low-titer pathogens - Devin A. Bowes; Katherine B. Henke; Erin M. Driver; Melanie Engstrom Newell; Izabella Block; Gray Shaffer; Arvind Varsani; Matthew Scotch; Rolf U. Halden (Science of The Total Environment, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Large scale seasonal forecasting of peak season algae metrics in the Midwest and Northeast U.S. - Maxwell R.W. Beal; Grace M. Wilkinson; Paul J. Block (Water Research, 2023)

Ecological lags govern the pace and outcome of plant community responses to 21st‐century climate change - Sebastián Block; Marc‐Jacques Maechler; Jacob I. Levine; Jake M. Alexander; Loïc Pellissier; Jonathan M. Levine (Ecology Letters, 2022)
Forecasting the trajectories of species assemblages in response to ongoing climate change requires quantifying the time lags in the demographic and ecological processes through which climate impacts species' abundances. Since experimental climate manipulations are typically abrupt, the observed species responses may not match their responses to gradual climate change. We addressed this problem by transplanting alpine grassland turfs to lower elevations, recording species' demographic responses to climate and competition, and using these data to parameterise community dynamics models forced by scenarios of gradual climate change. We found that shifts in community structure following an abrupt climate manipulation were not simply accelerated versions of shifts expected under gradual warming, as the former missed the transient rise of species benefiting from moderate warming. Time lags in demography and species interactions controlled the pace and trajectory of changing species' abundances under simulated 21st‐century climate change, and thereby prevented immediate diversity loss.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

Behavior and Ecology of Silky Sharks Around the Chagos Archipelago and Evidence of Indian Ocean Wide Movement - David J. Curnick; Samantha Andrzejaczek; David M. P. Jacoby; Daniel M. Coffey; Aaron B. Carlisle; Taylor K. Chapple; Francesco Ferretti; Robert J. Schallert; Timothy White; Barbara A. Block; Heather J. Koldewey; Ben Collen (Frontiers in Marine Science, 2020)
Silky sharks ( Carcharhinus falciformis ) represent a major component of global shark catch, both directly and as bycatch, and populations are declining as a result. An improved understanding of their movement ecology is needed to support conservation efforts. We deployed satellite and acoustic tags (2013–2018) and analyzed historical fisheries records (1997–2009), to investigate the spatial ecology of silky sharks in the central Indian Ocean and a large Marine Protected Area (MPA; 640,000 km 2 ) around the Chagos Archipelago. We observed high fidelity to the MPA, and a sustained diurnal association with a seamount complex, with individuals moving off at night and returning at sunrise. Yet, we also observed large-scale divergent movements in two satellite tagged individuals and documented the furthest recorded displacement distance for a satellite tagged silky shark to date, with one individual moving from the MPA to the Kenyan coast—a displacement distance of 3,549 km (track distance ∼4,782 km). Silky sharks undertook diel vertical migrations and oscillatory diving behavior, spending > 99% of their time in the top 100 m, and diving to depths of greater than 300 m, overlapping directly with typical deployments of purse seine and longline sets in the Indian Ocean. One individual was recorded to a depth of 1,112 m, the deepest recorded silky shark dive to date. Individuals spent 96% of their time at liberty within water temperatures between 24 and 30°C. Historic fisheries data revealed that silky sharks were a major component of the shark community around the archipelago, representing 13.69% of all sharks caught by longlines before the fishery closed in 2010. Over half (55.88%) of all individuals caught by longlines and purse seiners were juveniles. The large proportion of juveniles, coupled with the high site fidelity and residence observed in some individuals, suggests that the MPA could provide considerable conservation benefits for silky sharks, particularly during early life-history stages. However, their high mobility potential necessitates that large MPAs need to be considered in conjunction with fisheries regulations and conservation measures in adjacent EEZs and in areas beyond national jurisdiction.

Correction to: Genes associated with survival of female bovine blastocysts produced in vivo - A. M. Zolini; J. Block; M. B. Rabaglino; G. Rincon; M. Hoelker; J. J. Bromfield; D. Salilew-Wondim; P. J. Hansen (Cell and Tissue Research, 2020)

Genes associated with survival of female bovine blastocysts produced in vivo - A. M. Zolini; J. Block; M. B. Rabaglino; G. Rincon; M. Hoelker; J. J. Bromfield; D. Salilew-Wondim; P. J. Hansen (Cell and Tissue Research, 2020)

Long‐range reservoir inflow forecasts using large‐scale climate predictors - Amir M. Moradi; Alireza B. Dariane; Guang Yang; Paul Block (International Journal of Climatology, 2020)
Identifying significant large‐scale climate indicators has the potential to improve long‐range streamflow forecasts. In this research, we develop streamflow forecasts for Lake Urmia basin, Iran, specifically for inflow into the Boukan and Mahabad reservoirs. In doing so, two types of inflow forecast models are considered: a single site univariate model ignoring the cross correlation between streamflow at different stations, and a multi‐site multivariate forecast model which takes into consideration the cross correlations among stations. Predictor selection is performed through a principal component analysis and an adaptive‐network‐based fuzzy inference system is used to forecast streamflow. Forecast performance is investigated by employing different combinations of large‐scale climatic information and hydrologic data. We found that gridded ocean‐atmospheric circulation variables, including surface precipitation rate and omega (pressure vertical velocity), have the highest correlations (about 0.7) with annual streamflow. In general, multivariate models are able to better preserve the annual cross‐correlations between streamflow at different stations, as expected, without sacrificing forecast skill as compared to the univariate forecast model approach. Additionally, as compared with the baseline feed‐forward artificial neural network‐ and traditional multiple linear regression‐forecast models, the results were approximately the same. This similarity in the forecast performance between the linear and nonlinear models is likely due to the short of data (44‐sample record).

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Biosynthesis and function of terpenoid defense compounds in maize (Zea mays) - Anna K. Block; Martha M. Vaughan; Eric A. Schmelz; Shawn A. Christensen (Planta, 2019)

Fungal and herbivore elicitation of the novel maize sesquiterpenoid, zealexin A4, is attenuated by elevated CO2 - Shawn A. Christensen; Alisa Huffaker; James Sims; Charles T. Hunter; Anna Block; Martha M. Vaughan; Denis Willett; Maritza Romero; J. Erik Mylroie; W. Paul Williams; Eric A. Schmelz (Planta, 2018)

The effects of climate change associated abiotic stresses on maize phytochemical defenses - Martha M. Vaughan; Anna Block; Shawn A. Christensen; Leon Hartwell Allen; Eric A. Schmelz (Phytochemistry Reviews, 2018)

Calcium Phosphate Particles as Pulmonary Delivery System for Interferon-α in Mice - Tülin Morçöl; Jessica M. Weidner; Anand Mehta; Stephen J.D. Bell; Timothy Block (AAPS PharmSciTech, 2018)

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Impacts of Hemlock Loss on Nitrogen Retention Vary with Soil Nitrogen Availability in the Southern Appalachian Mountains - Corinne E. Block; Jennifer D. Knoepp; Katherine J. Elliott; Jennifer M. Fraterrigo (Ecosystems, 2012)

Development of the mandibular, hyoid arch and gill arch skeleton in the Chinese barb Puntius semifasciolatus : comparisons of ossification sequences among Cypriniformes - A. J. Block; P. M. Mabee (Journal of Fish Biology, 2012)
The morphogenesis and sequence of ossification and chondrification of skeletal elements of the jaws, and hyoid arch and gill arches of Puntius semifasciolatus are described. These data provide a baseline for further studies and enable comparisons with other described cypriniforms. Some general patterns of ossification in the hyoid arch and branchial arches in cypriniforms were notable. First, the overall development is from anterior to posterior, with the exception of the fifth ceratobranchial bone, which ossifies first. Second, where ossification of iterated elements is sequential, it tends to proceed from posterior to anterior, even when more posterior chondrifications are the smallest in the series. Ossification of the ceratobranchial, epibranchial and pharyngobranchial bones tends to proceed from ventral to dorsal. The comparisons revealed small sets of skeletal elements whose ossification sequence appears to be relatively conserved across cyprinid cypriniforms. Several potentially key timing changes in the ossification sequence of the jaws, hyoid arch and gill arches were identified, such as the accelerated timing of ossification of the fifth ceratobranchial bone, which may be unique to cypriniforms.

Direct evidence that HSV DNA damaged by ultraviolet (UV) irradiation can be repaired in a cell type-dependent manner - Scott Millhouse; Xiaohe Wang; Nigel W. Fraser; Lisa Faber; Timothy M. Block (Journal of NeuroVirology, 2012)

Enhanced phosphorylation of caveolar PKC-α limits peptide internalization in lung endothelial cells - Tarun E. Hutchinson; Jianliang Zhang; Shen-Ling Xia; Sudeep Kuchibhotla; Edward R. Block; Jawaharlal M. Patel (Molecular and Cellular Biochemistry, 2012)

Genetic variants in the folate pathway and risk of childhood acute lymphoblastic leukemia - Catherine Metayer; Ghislaine Scélo; Anand P. Chokkalingam; Lisa F. Barcellos; Melinda C. Aldrich; Jeffrey S. Chang; Neela Guha; Kevin Y. Urayama; Helen M. Hansen; Gladys Block; Vincent Kiley; John K. Wiencke; et al. (Cancer Causes & Control, 2011)

Relevance of Rheological Properties of Sodium Alginate in Solution to Calcium Alginate Gel Properties - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Ira S. Buckner; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Erratum: Rheological Evaluation of Inter-Grade and Inter-Batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Rheological Evaluation of Inter-grade and Inter-batch Variability of Sodium Alginate - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2010)

Endothelial arginase II responds to pharmacological inhibition by elevation in protein level - Karina Krotova; Jawaharlal M. Patel; Edward R. Block; Sergey Zharikov (Molecular and Cellular Biochemistry, 2010)

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

Mitochondrial DNA and electronic tracking reveal population structure of Atlantic bluefin tuna (Thunnus thynnus) - Andre M. Boustany; Carol A. Reeb; Barbara A. Block (Marine Biology, 2008)

Tumor-associated protein SPIK/TATI suppresses serine protease dependent cell apoptosis - Xuanyong Lu; Jason Lamontagne; Felix Lu; Timothy M. Block (Apoptosis, 2008)

Nitric oxide upregulation of caspase-8 mRNA expression in lung endothelial cells: role of JAK2/STAT-1 signaling - Liuzhe Li; Jianliang Zhang; Bilian Jin; Edward R. Block; Jawaharlal M. Patel (Molecular and Cellular Biochemistry, 2007)

Oceanographic preferences of Atlantic bluefin tuna, Thunnus thynnus, on their Gulf of Mexico breeding grounds - Steven L. H. Teo; Andre M. Boustany; Barbara A. Block (Marine Biology, 2007)

Migration and habitat of white sharks (Carcharodon carcharias) in the eastern Pacific Ocean - Kevin C. Weng; Andre M. Boustany; Peter Pyle; Scot D. Anderson; Adam Brown; Barbara A. Block (Marine Biology, 2007)

Movements, behavior, and habitat utilization of yellowfin tuna (Thunnus albacares) in the northeastern Pacific Ocean, ascertained through archival tag data - Kurt M. Schaefer; Daniel W. Fuller; Barbara A. Block (Marine Biology, 2007)

Horizontal and vertical movements of juvenile bluefin tuna ( Thunnus orientalis ) in relation to seasons and oceanographic conditions in the eastern Pacific Ocean - TAKASHI KITAGAWA; ANDRE M. BOUSTANY; CHARLES J. FARWELL; THOMAS D. WILLIAMS; MICHAEL R. CASTLETON; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Electronically tagged juvenile Pacific bluefin, Thunnus orientalis , were released off Baja California in the summer of 2002. Time‐series data were analyzed for 18 fish that provided a record of 380 ± 120 days (mean ± SD) of ambient water and peritoneal cavity temperatures at 120 s intervals. Geolocations of tagged fish were estimated based on light‐based longitude and sea surface temperature‐based latitude algorithms. The horizontal and vertical movement patterns of Pacific bluefin were examined in relation to oceanographic conditions and the occurrence of feeding events inferred from thermal fluctuations in the peritoneal cavity. In summer, fish were located primarily in the Southern California Bight and over the continental shelf of Baja California, where juvenile Pacific bluefin use the top of the water column, undertaking occasional, brief forays to depths below the thermocline. In autumn, bluefin migrated north to the waters off the Central California coast when thermal fronts form as the result of weakened equatorward wind stress. An examination of ambient and peritoneal temperatures revealed that bluefin tuna fed during this period along the frontal boundaries. In mid‐winter, the bluefin returned to the Southern California Bight possibly because of strong downwelling and depletion of prey species off the Central California waters. The elevation of the mean peritoneal cavity temperature above the mean ambient water temperature increased as ambient water temperature decreased. The ability of juvenile bluefin tuna to maintain a thermal excess of 10°C occurred at ambient temperatures of 11–14°C when the fish were off the Central California coast. This suggests that the bluefin maintain peritoneal temperature by increasing heat conservation and possibly by increasing internal heat production when in cooler waters. For all of the Pacific bluefin tuna, there was a significant correlation between their mean nighttime depth and the visible disk area of the moon.

Herpes simplex virus type 1 ICP4 deletion mutant virus d120 infection failed to induce apoptosis in nerve growth factor–differentiated PC12 cells - Benjamas Aiamkitsumrit; Xianchao Zhang; Timothy M Block; Pamela Norton; Nigel W Fraser; Ying-Hsiu Su (Journal of NeuroVirology, 2007)

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

The stability of herpes simplex virus type I genomes in infected Vero cells undergoing viral induced apoptosis - Ying-Hsiu Su; Xianchao Zhang; Benjamas Aiamkitsumrit; Qiyi Tang; Gerd Maul; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2006)

A review: dietary and endogenously formed N-nitroso compounds and risk of childhood brain tumors - Marion Dietrich; Gladys Block; Janice M. Pogoda; Patricia Buffler; Stephen Hecht; Susan Preston -Martin (Cancer Causes & Control, 2005)

Angiotensin IV enhances phosphorylation of 4EBP1 by multiple signaling events in lung endothelial cells - Jianghua Lu; Jianalian Zhang; Edward R. Block; Jawaharlal M. Patel (Molecular and Cellular Biochemistry, 2005)

Characterization of Aspen ASH, Sand and Log-Yard Waste Mixtures from an Aspen-Based Oriented Strand Board Mill for Use as an Intermediate Landfill Cover - R. M. A. Block; K. C. J. van Rees (Water, Air, & Soil Pollution, 2004)

Mechanized land preparation in forest-based fallow systems: The experience from Eastern Amazonia - M. Denich; K. Vielhauer; M.S. de A. Kato; A. Block; O.R. Kato; T.D. de Abreu Sá; W. Lücke; P.L.G. Vlek (Agroforestry Systems, 2004)

Thioredoxin restores nitric oxide-induced inhibition of protein kinase C activity in lung endothelial cells - Katriina Kahlos; Jianliang Zhang; Edward R. Block; Jawaharlal M. Patel (Molecular and Cellular Biochemistry, 2003)

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Biofilms in Drinking Water Distribution Systems - M. Batté; B.M.R. Appenzeller; D. Grandjean; S. Fass; V. Gauthier; F. Jorand; L. Mathieu; M. Boualam; S. Saby; J.C. Block (Reviews in Environmental Science and Bio/Technology, 2003)

Does the cerebellum play a role in podokinetic adaptation? - Gammon M. Earhart; William A. Fletcher; Fay B. Horak; Edward W. Block; Kimberly D. Weber; Oksana Suchowersky; Geoffrey Melvill Jones (Experimental Brain Research, 2002)

Cluster of Neonatal Infections in Jerusalem due to Unusual Biochemical Variant of Enterobacter sakazakii - C. Block; O. Peleg; N. Minster; B. Bar-Oz; A. Simhon; I. Arad; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Behaviour of a sharptail mola in the Gulf of Mexico - A. C. Seitz; K. C. Weng; A. M. Boustany; B. A. Block (Journal of Fish Biology, 2002)
A sharptail mola Masturus lanceolatus was tagged and released with a pop‐up satellite archival tag in the Gulf of Mexico and tracked for 61 days. The fish travelled a horizontal distance of 594 km while generally staying in water 20° C. Occasionally the sharptail mola dived to depths >700 m and experienced water colder than 6° C.

Increasing Incidence of Gonorrhea in Israel Associated with Countrywide Dissemination of a Ciprofloxacin-Resistant Strain - Yagupsky P.; Schahar A.; Peled N.; Porat N.; Trefler R.; Dan M.; Keness Y.; Block C. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Adaptive Management on Public Lands in the United States: Commitment or Rhetoric? - W. H. MOIR; W. M. BLOCK (Environmental Management, 2001)

Metal Pollution and Fat Accumulation in the Carabid Beetle Pterostichus melanarius (Coleoptera, Carabidae) - L. Lindqvist; M. Block (Bulletin of Environmental Contamination and Toxicology, 2001)

Gas and fluid venting at the Makran accretionary wedge off Pakistan - U. von Rad; U. Berner; G. Delisle; H. Doose-Rolinski; N. Fechner; P. Linke; A. Lückge; H. A. Roeser; R. Schmaljohann; M. Wiedicke; SONNE 122/130 Scientific Parties; M. Block; et al. (Geo-Marine Letters, 2000)

Factors Associated with Nosocomial Diarrhea and Clostridium difficile -Associated Disease on the Adult Wards of an Urban Tertiary Care Hospital - M. J. Schwaber; A. Simhon; C. Block; V. Roval; N. Ferderber; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Thermal tolerance and acclimation response of larvae of the sub-Antarctic beetle Hydromedion sparsutum (Coleoptera: Perimylopidae) - J. S. Bale; W. Block; M. R. Worland (Polar Biology, 2000)

Syndromes of Global Change: a qualitative modelling approach to assist global environmental management - G. Petschel-Held; A. Block; M. Cassel-Gintz; J. Kropp; M.K.B. Lüdeke; O. Moldenhauer; F. Reusswig; H.J. Schellnhuber (Environmental Modeling & Assessment, 1999)

Outbreak of Bloodstream Infections Associated with Dialysis Machine Waste Ports in a Hemodialysis Facility - C. Block; R. Backenroth; E. Gershon; R. Israeli; A. Simhon; M. Popovtzer; M. Shapiro (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Renal handling of drugs in the healthy elderly - D. Fliser; I. Bischoff; A. Hanses; S. Block; M. Joest; E. Ritz; E. Mutschler (European Journal of Clinical Pharmacology, 1999)

Mexican Spotted Owl Home Range and Habitat Use in Pine-Oak Forest: Implications for Forest Management - Joseph L. Ganey; William M. Block; Jeffrey S. Jenness; Randolph A. Wilson (Forest Science, 1999)
To better understand the habitat relationships of the Mexican spotted owl (Strix occidentalis lucida), and how such relationships might influence forest management, we studied home-range and habitat use of radio-marked owls in ponderosa pine (Pinus ponderosa)-Gambel oak (Quercus gambelii) forest. Annual home-range size (95% adaptive-kernel estimate) averaged 895 ha ± + 70 (SE) for 12 individuals and 997 ha ± 186 (SE) for 7 pairs of owls. On average, the 75% adaptive-kernel contour (a probability contour containing 75% of the owl locations) included 32 and 30% of the annual home range for individuals and pairs, respectively, suggesting high concentration of activity in a relatively small portion of the home range. Relative area of three cover types (ponderosa pine forest, pine-oak forest, and meadow) did not differ between seasonal ranges, and owls used these cover types in proportion to their relative area during both breeding and nonbreeding seasons. In contrast, relative area of four canopy-cover classes varied between seasons. Breeding-season ranges contained greater proportions of areas with canopy cover ≥ 60% and lower proportions of areas with 20-39% canopy cover than nonbreeding-season ranges. Owls roosted and foraged in stands with ≥ 60% canopy cover more than expected during both breeding and nonbreeding seasons, and used stands with 20-39% canopy cover less than expected except for foraging during the breeding season. Stands used for foraging did not differ in structure between seasons and had greater canopy cover and less rock cover than stands with no documented use. Stands used for roosting differed between seasons in a multivariate comparison, but no individual habitat variables differed between seasons in subsequent univariate comparisons. In both seasons, stands used for roosting had greater canopy cover than stands with no roosting use. Closed-canopy forests, which were used heavily by owls, were relatively rare on the study area, suggesting that such forests warrant special protection in areas managed for spotted owls. This may conflict with efforts to restore more open conditions in ponderosa pine forests. For. Sci. 45(1):127-135.

Development and Evaluation of Habitat Models for Herpetofauna and Small Mammals - William M. Block; Michael L. Morrison; Peter E. Scott (Forest Science, 1998)
We evaluated the ability of discriminant analysis (DA), logistic regression (LR), and multiple regression (MR) to describe habitat use by amphibians, reptiles, and small mammals found in California oak woodlands. We also compared models derived from pitfall and live trapping data for several species. Habitat relations modeled by DA and LR produced similar results, averaging about 70% classification success of the trapping stations to the correct group (capture or noncapture habitat). Although more variables were included in DA (4-5) than in LR (2-3), those included in LR were typically a subset of those in DA. On average, MR habitat models accounted for 56% of the variation in the index of relative species' abundance. The variables included in the MR models were seldom the same as those for DA and LR. Most differences between MR and the other two methods were related to differences in spatial scale: MR modeled habitat among grids, whereas DA and LR modeled habitat within grids. Habitat models for the same species differed between the trapping methods used. Live traps are most useful for describing general habitat relations of some small mammal species across large geographic areas, whereas pitfall traps are useful for intensive sampling of a larger portion of the vertebrate community within smaller geographic areas. Thus, the choice of trapping methods must be based on the study goals, biology of the species, and the spatial scale of study. For. Sci. 44(3):430-437.

Sex Specific Interactions Between Cd and Zn in Three Beetle Species (Insecta, Coleoptera) - L. Lindqvist; M. Block (Bulletin of Environmental Contamination and Toxicology, 1998)

The development of a nuclear male sterility system in wheat. Expression of the barnase gene under the control of tapetum specific promoters - M. De Block; D. Debrouwer; T. Moens (Theoretical and Applied Genetics, 1997)

Influence of Life History and Sex on Metal Accumulation in Two Beetle Species (Insecta: Coleoptera) - L. Lindqvist; M. Block (Bulletin of Environmental Contamination and Toxicology, 1997)

Losses of Cd, Hg, and Zn During Metamorphosis in the Beetle Tenebrio Molitor (Coleoptera: Tenebrionidae) - L. Lindqvist; M. Block (Bulletin of Environmental Contamination and Toxicology, 1997)